Conductive paste, electronic component, and multilayer ceramic capacitor
The conductive paste formulation addresses the challenges of dispersion and viscosity in small particle size conductive powders by using a specific additive structure and organic solvent, resulting in improved dispersibility and printing performance for multilayer ceramic capacitors.
Patent Information
- Application Number
- JP2023144173
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
Conductive pastes using small particle size conductive powders face challenges with insufficient dispersion, leading to coarse particle formation and potential short circuits in multilayer ceramic capacitors, while increasing additives to improve dispersion can result in reduced shear viscosity and printing issues.
A conductive paste formulation that includes a conductive powder with a number average particle diameter of 120 nm or less, a binder resin, an additive with a chain type hydrocarbon group and at least one structure selected from phosphoric acid, carboxylic acid, and β-keto ester, and an organic solvent, achieving a shear viscosity of 20 Pa·s or more and 60 Pa·s or less, suitable for printing.
The conductive paste effectively suppresses coarse particle formation, maintains suitable shear viscosity for printing, and ensures good dispersibility of conductive powders, thereby reducing the risk of short circuits and improving the performance of multilayer ceramic capacitors.
Smart Images

Figure 2025037318000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. [Background technology]
[0002] As electronic devices such as mobile phones and digital devices become lighter, thinner, shorter, and smaller, there is a demand for electronic components such as multilayered ceramic capacitors (hereinafter referred to as "MLCCs") to be smaller, have higher capacitance, and have higher performance. For example, one method for achieving the miniaturization and high capacitance of multilayered ceramic capacitors is to make the internal electrode layers and dielectric layers thinner to create multiple layers.
[0003] A multilayer ceramic capacitor is manufactured, for example, as follows. First, in order to form a dielectric layer, a dielectric green sheet is formed using a dielectric ceramic powder such as barium titanate (BaTiO3) as a main component, and a binder resin made of a butyral resin such as polyvinyl butyral or an acrylic resin. Next, a conductive paste for an internal electrode formed by dispersing a conductive powder in an organic vehicle containing a binder resin and an organic solvent is printed in a predetermined pattern on the surface of the dielectric green sheet, and dried to remove the organic solvent, forming a dry film that becomes an internal electrode layer on the dielectric green sheet. Next, the dry film and the dielectric green sheet are stacked in multiple layers, and in this state, they are integrated by heat and pressure bonding to form a pressure-bonded body. Then, the pressure-bonded body is cut to a predetermined size to obtain a chip. Next, the chip is subjected to a binder removal treatment at 500°C or less in an oxidizing atmosphere or an inert atmosphere. Then, the chip after the binder removal treatment is heated and fired at about 1300°C in a reducing atmosphere so as not to oxidize the internal electrode layer, and the internal electrode layer and the dielectric layer are integrated to obtain a fired chip. Finally, a paste for external electrodes is applied to the fired chip and fired, and the resulting external electrodes are then plated with nickel or the like to complete the multilayer ceramic capacitor.
[0004] Conductive paste for internal electrodes is generally obtained by dispersing conductive powder, ceramic powder, and additives in an organic vehicle obtained by dissolving a binder resin in an organic solvent, and adjusting the viscosity with the organic solvent. Ethyl cellulose or the like is generally used as the binder resin constituting this organic vehicle, and terpineol or the like has been used as the organic solvent (e.g., Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-031912 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, as the miniaturization of electronic components has led to thinner electrode patterns, there has been a demand for conductive pastes that use conductive powders with smaller particle sizes than before.
[0007] However, conductive pastes using conductive powder with a small particle size (for example, an average particle size of 120 nm or less) have an increased surface energy, which can result in insufficient dispersion of the conductive powder in the conductive paste. For example, when using a thin-film electrode pattern in a multilayer ceramic capacitor, if coarse particles formed due to insufficient dispersion of the conductive powder remain in the internal electrode layer, there is a concern that when the internal electrode layer and the dielectric layer are laminated, the coarse particles may damage the dielectric layer, causing defects such as short circuits.
[0008] In order to disperse the conductive powder sufficiently, for example, an additive (e.g., a dispersant, etc.) may be increased to improve the dispersibility of the conductive powder. However, when a large amount of additive is added to improve the dispersibility of the conductive powder, the shear viscosity of the conductive paste decreases, and a problem of the solvent seeping out after printing the electrode pattern may occur.
[0009] The present invention has been made in consideration of the above problems, and aims to provide a conductive paste that suppresses the formation of coarse particles in the conductive paste even when a conductive powder with a small particle size is used, and has a shear viscosity suitable for printing. [Means for solving the problem]
[0010] The conductive paste according to one embodiment of the present invention includes a conductive powder, a binder resin, an additive, and an organic solvent, the additive having a structure (A) of a chain hydrocarbon group having 5 to 9 carbon atoms and at least one structure (B) selected from phosphoric acid, carboxylic acid, and β-ketoester, and does not contain a N atom, and the conductive paste has a shear rate of 4 s at 25° C. -1 The shear viscosity is 20 Pa s or more and 60 Pa s or less.
[0011] The content of the additive with respect to 100 parts by mass of the conductive powder may be 0.01 parts by mass or more and 4 parts by mass or less. The content of the conductive powder with respect to the total amount of the conductive paste may be 40% by mass or more and 65% by mass or less. The number average particle diameter of the conductive powder may be 120 nm or less. The conductive powder may be at least one selected from gold powder, silver powder, palladium powder, copper powder, nickel powder, aluminum powder, silver-palladium alloy powder, copper alloy powder, and aluminum alloy powder. The binder resin may include at least one selected from cellulose-based resin and acetal-based resin. The content of the organic solvent with respect to the total amount of the conductive paste may be 20% by mass or more and 60% by mass or less. The conductive paste may include ceramic powder. The ceramic powder may be at least one selected from aluminum oxide powder, zinc oxide powder, titanium oxide powder, mullite powder, barium titanate powder, lead zirconate titanate powder, and silicate glass powder.
[0012] An electronic component according to an aspect of the present invention is formed using the conductive paste.
[0013] A multilayer ceramic capacitor according to one aspect of the present invention includes at least a laminate in which dielectric layers and internal electrode layers are laminated, and the internal electrode layers are formed using the above-mentioned conductive paste. Effect of the Invention
[0014] According to the conductive paste of the present invention, even when a conductive powder having a small particle size is used, the formation of coarse particles in the conductive paste can be suppressed, and a conductive paste capable of obtaining a shear viscosity suitable for printing can be provided. [Brief description of the drawings]
[0015] [Figure 1] 1 is a perspective view showing a multilayer ceramic capacitor using the conductive paste of the present invention. [Diagram 2]1 is a side cross-sectional view showing a multilayer ceramic capacitor using the conductive paste of the present invention. [Diagram 3] 1 is a surface observation image of a dried film using the conductive paste of Example 1. [Figure 4] 1 is a surface observation image of a dried film using the conductive paste of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the conductive paste of the present invention and a multilayer ceramic capacitor as an electronic component using the conductive paste of the present invention will be described.
[0017] The conductive paste of the present embodiment includes a conductive powder, a binder resin, an additive, and an organic solvent. The conductive paste may further include a ceramic powder. Each component of the conductive paste of the present embodiment will be described in detail below.
[0018] [Conductive powder] The conductive powder is not particularly limited, and metal powder can be used. For example, one or more metal powders selected from Au powder, Ag powder, Pd powder, Cu powder, Ni powder, Al powder, and alloys thereof can be used. Among these, Ni powder or Ni alloy powder is preferable from the viewpoints of conductivity, corrosion resistance, and cost. As the Ni alloy, for example, an alloy of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt, and Pd (Ni alloy) can be used. The Ni content in the Ni alloy is, for example, 50 mass% or more, preferably 80 mass% or more. In addition, the Ni powder or Ni alloy powder may contain about several hundred ppm of S in order to suppress rapid gas generation due to partial thermal decomposition of the binder resin during the binder removal process.
[0019] The number average particle size of the conductive powder is not particularly limited, but may be, for example, 120 nm or less, 100 nm or less, or 90 nm or less. When the average particle size of the conductive powder is within the above range, it can be suitably used as a conductive paste for thin electrodes, and the smoothness of the dried film is improved. In a conventional conductive paste, when a conductive powder with a small particle size is used, the dispersibility decreases due to an increase in surface energy, and coarse particles may be easily formed. On the other hand, in the conductive paste according to the present embodiment, even when a conductive powder with a small particle size is used, the paste has good dispersibility and can suppress the formation of coarse particles.
[0020] The number average particle size of the conductive powder is preferably 30 nm to 100 nm, more preferably 40 nm to 90 nm. When the number average particle size of the conductive powder is in the above range, an increase in the number of secondary particles (aggregates) formed by aggregation of the conductive powder can be suppressed, and the coarsening of the secondary particles (aggregates) can be suppressed.
[0021] The number average particle size can be measured as follows. The conductive powder is photographed using a scanning electron microscope (SEM) (6360A, manufactured by JEOL Ltd.) to obtain an SEM image. From the obtained SEM image, the particle size of 1000 or more particles of the conductive powder is measured using image analysis type particle size distribution measurement software (Mac-View, manufactured by Mountec Co., Ltd.), and then the area circle equivalent diameter (Heywood diameter) is calculated for each conductive powder, and the number average particle size in the number-based particle size distribution is obtained.
[0022] The content of the conductive powder is, for example, 35% by mass or more and 70% by mass or less, preferably 40% by mass or more and 65% by mass or less, and more preferably 45% by mass or more and 60% by mass or less, based on the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent, and the viscosity of the conductive paste can be easily adjusted to a suitable range.
[0023] [Binder resin] The binder resin is not particularly limited, and known resins can be used. Examples of the binder resin include cellulose-based resins such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and nitrocellulose, acrylic resins, and acetal-based resins such as polyvinyl butyral. One type of binder resin may be used, or two or more types may be used. For example, the binder resin may be a cellulose-based resin and an acetal-based resin. Among them, it is preferable to include a cellulose-based resin from the viewpoint of solubility in a solvent and combustion decomposition, and it is more preferable to include ethyl cellulose. In addition, when used as a conductive paste for internal electrodes, it may include an acetal-based resin from the viewpoint of improving the adhesive strength with the green sheet, and the acetal-based resin is preferably a butyral-based resin.
[0024] The polymerization degree and weight-average molecular weight of the binder resin can be appropriately adjusted within the above ranges according to the required viscosity of the conductive paste. For example, when the binder resin contains a cellulose-based resin, the weight-average molecular weight of the binder resin is preferably about 20,000 to 300,000, more preferably about 30,000 to 300,000. When the weight-average molecular weight is within the above range, it is easy to adjust the viscosity to a suitable range for screen printing while ensuring compatibility between the resins and with organic solvents, and a conductive paste with improved printability can be obtained. In addition, it is also possible to reduce residual carbon after firing.
[0025] The content of the binder resin is preferably 0.5% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 10% by mass or less, and even more preferably 1% by mass or more and 6% by mass or less, based on the entire conductive paste. When the content of the binder resin is within the above range, the conductive paste has better conductivity and dispersibility.
[0026] [Additives] The additive according to the present embodiment has a structure (A) of a chain hydrocarbon group having 5 to 9 carbon atoms (hereinafter, also simply referred to as "structure (A)") and at least one structure (B) selected from phosphoric acid, carboxylic acid, and β-ketoester (hereinafter, also simply referred to as "structure (B)"). The additive may be one that does not contain a N atom. Two or more types of additives may be used in combination, if necessary.
[0027] For example, when the conductive powder used in the conductive paste has a small particle size (e.g., 120 nm or less, or 100 nm or less), the surface area of the entire conductive powder increases compared to the conductive powder of the same mass with a large particle size, but the surface area of each particle is small. Therefore, the amount of additives that are coordinated to the surface of one conductive powder particle decreases, so that dispersibility tends to decrease. In order to improve dispersibility, it is sufficient to increase the amount of additives blended, but as the amount of additives blended increases, the shear viscosity of the conductive paste decreases, making it difficult to achieve both dispersibility and a desired shear viscosity. By using an additive having the above specific structure, the conductive paste according to this embodiment has excellent dispersibility even for a conductive powder with a small particle size, and the viscosity of the conductive paste can be controlled to a shear viscosity suitable for screen printing. The additive according to this embodiment will be described in detail below.
[0028] The additive has at least one type of structure (B) selected from phosphoric acid, carboxylic acid, and β-ketoester. Structure (B) has a double bond of oxygen atom O and two lone pairs at the same time. Although the details of the mechanism are unknown, it is presumed that the dispersion is improved by the coordination bond between the conductive powder and the additive through these two lone pairs. On the other hand, when the additive contains nitrogen atom N, the nitrogen atom N has one lone pair of electrons, so the coordination bond is weaker than when the additive contains oxygen atom O, and the dispersion effect is inferior.
[0029] Examples of the additive component (B) include hexyl phosphate, heptyl phosphate, octyl phosphate, nonyl phosphate, decyl phosphate, hexanoic acid, heptanoic acid, 2-ethylhexanoic acid, n-octanoic acid, nonanoic acid, decanoic acid, hexyl acetoacetate, heptyl acetoacetate, octyl acetoacetate, nonyl acetoacetate, and decyl acetoacetate.
[0030] The additive also has a structure (A) of a chain hydrocarbon group having 5 to 9 carbon atoms. Although the details of the mechanism are unknown, it is presumed that the additive, by having structure (A) in combination with structure (B), becomes more compatible with organic solvents, thereby improving dispersibility. On the other hand, if the number of carbon atoms in the chain hydrocarbon group is less than 5, the hydrophilicity becomes high and compatibility with organic solvents becomes poor, resulting in a decrease in dispersibility. Also, if the number of carbon atoms in the chain hydrocarbon group is more than 9, the main chain becomes too long and the chain is not fully extended and becomes in a shrunken state, suppressing the occurrence of steric repulsion due to steric hindrance, and a large number of coarse particles are formed, particularly in pastes containing conductive powders with small particle diameters, which may decrease dispersibility and increase the paste viscosity.
[0031] The chain hydrocarbon group of the structure (A) may be an unsaturated hydrocarbon group or a saturated hydrocarbon group, but is preferably a saturated hydrocarbon group. The chain hydrocarbon group of the structure (A) may be a straight chain or a branched chain.
[0032] The molecular weight of the additive is not particularly limited as long as it has the above structure, but is preferably 100 or more and 300 or less.
[0033] The additive is preferably contained in an amount of 0.01 to 5 parts by mass, more preferably 0.01 to 4 parts by mass, relative to 100 parts by mass of the conductive powder, and more preferably 0.02 to 3 parts by mass. When the additive content is within the above range, the dispersibility of the conductive powder in the conductive paste is improved, and the formation of coarse particles due to aggregation can be suppressed, thereby reducing the occurrence of defects such as short circuits. In addition, since the dispersibility can be improved without using an excessive amount of additive, the paste viscosity can be controlled to be suitable for screen printing.
[0034] If the content of the additive is too high, the dispersion of the conductive powder in the conductive paste is sufficient, but the viscosity of the conductive paste may be too low. If the viscosity of the conductive paste is too low, it may be difficult to apply the conductive paste to the green sheet, or the adhesion between the green sheet and the dried paste film may be poor. In addition, residual carbon may remain even after the firing process, which may affect the electrical properties of the multilayer ceramic capacitor. The content of the additive may be appropriately adjusted depending on the particle size, type, etc. of the conductive powder.
[0035] [Organic solvents] The organic solvent is not particularly limited, and any known organic solvent capable of dissolving the binder resin can be used.
[0036] Examples of organic solvents include acetate-based solvents such as dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, and dipropylene glycol methyl ether acetate, terpene-based solvents such as terpineol, dihydroterpineol, and dihydroterpineol acetate, and hydrocarbon-based solvents such as tridecane, nonane, and cyclohexane. The organic solvent preferably contains a terpene-based solvent, and more preferably contains dihydroterpineol. The organic solvent may be one type or two or more types.
[0037] The content of the organic solvent in the conductive paste is preferably 20% by mass or more and 60% by mass or less based on the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0038] [Ceramic powder] When the conductive paste according to this embodiment is used as an internal electrode of a multilayer ceramic capacitor, the conductive paste may further contain ceramic powder.
[0039] The ceramic powder is not particularly limited. For example, in the case of a conductive paste for an internal electrode of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected depending on the type of multilayer ceramic capacitor to be applied. Examples of such ceramic powder include aluminum oxide powder, zinc oxide powder, titanium oxide powder, mullite powder, barium titanate powder, lead zirconate titanate powder, and silicate glass powder, and barium titanate (BaTiO3) is particularly preferable. One type of ceramic powder may be used, or two or more types may be used.
[0040] In particular, it is advisable to use a powder having the same composition as the dielectric ceramic powder constituting the green sheet in the conductive paste for the internal electrodes of the multilayer ceramic capacitor, as this can prevent cracks from occurring due to a mismatch in shrinkage at the interface between the dielectric layer and the internal electrode layer during the sintering process.
[0041] The number average particle diameter of the ceramic powder is, for example, 10 nm to 100 nm, and preferably in the range of 10 nm to 70 nm. When the number average particle diameter of the ceramic powder is in the above range, when the ceramic powder is used as a conductive paste for an internal electrode, a sufficiently thin and uniform internal electrode can be formed. The number average particle diameter of the ceramic powder may be smaller than the number average particle diameter of the conductive powder. The number average particle diameter can be measured as follows. The ceramic powder is photographed using a scanning electron microscope (SEM) (6360A, manufactured by JEOL Ltd.) to obtain an SEM image. From the obtained SEM image, the particle size of 1000 or more particles of the ceramic powder is measured using image analysis type particle size distribution measurement software (Mac-View, manufactured by Mountec Co., Ltd.), and then the area circle equivalent diameter (Heywood diameter) of each ceramic powder is calculated to obtain the number average particle diameter in the particle size distribution based on the number.
[0042] The content of the ceramic powder is preferably 1% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 20% by mass or less, based on the entire conductive paste. When the content of the conductive powder is within the above range, the conductive paste has excellent electrical conductivity and sinterability.
[0043] [Other additives] The conductive paste according to this embodiment may contain known additives other than the above additives, such as dispersants, defoamers, plasticizers, thickeners, chelating agents, etc., depending on the purpose in order to control various characteristics.
[0044] (Conductive paste) The method for producing the conductive paste of the present embodiment is not particularly limited, and a conventionally known method can be used. The conductive paste can be produced, for example, by preparing each component of conductive powder, ceramic powder, binder resin, additive, and organic solvent, and stirring and kneading them with a three-roll mill, ball mill, mixer, or the like to disperse the conductive powder and ceramic powder. Alternatively, the binder resin may be dissolved in an organic solvent for a vehicle to produce an organic vehicle, and the conductive powder, ceramic powder, organic vehicle, and dispersant may be added to the organic solvent for a paste, and the mixture may be stirred and kneaded with a mixer to produce a conductive paste. In addition, the conductive paste according to the present embodiment may or may not support the additive on the surface of the conductive powder before mixing with other materials. The conductive paste according to the present embodiment has good dispersibility and can be produced more easily even without supporting the additive on the surface of the conductive powder.
[0045] Conductive paste is subjected to a shear rate of 4s at 25°C after 24 hours from the production of the conductive paste. -1 The shear viscosity when the conductive paste is applied is preferably 20 Pa·s or more and 60 Pa·s or less, and more preferably 25 Pa·s or more and 40 Pa·s or less. A shear viscosity in the above range is preferable when the conductive paste is used as an internal electrode in electronic components, and is particularly suitable for producing internal electrodes by screen printing. If the shear viscosity is less than 20 Pa·s, the printed conductive paste may bleed out. If the shear viscosity is more than 60 Pa·s, printing defects such as mesh marks may occur.
[0046] The shear viscosity of the conductive paste was measured, for example, by flow curve measurement using a rheometer MCR501 manufactured by Anton Paar at a rotation speed of 4 s -1 The measurement can be performed under the conditions described above.
[0047] The conductive paste can be suitably used in electronic components such as multilayer ceramic capacitors, varistors, etc. A multilayer ceramic capacitor has dielectric layers formed using dielectric green sheets and internal electrode layers formed using the conductive paste.
[0048] In the multilayer ceramic capacitor, the dielectric ceramic powder contained in the dielectric green sheet and the ceramic powder contained in the conductive paste are preferably powders of the same composition. In the multilayer ceramic device manufactured using the conductive paste of this embodiment, even if the thickness of the dielectric green sheet is, for example, 3 μm or less, sheet attack and peeling failure of the green sheet are suppressed.
[0049] [Electronic components] Hereinafter, embodiments of electronic components and the like that can be manufactured using the conductive paste of the present invention will be described with reference to the drawings. In the drawings, the components may be shown in schematic form or at a different scale as appropriate. The positions and directions of components will be described with reference to the XYZ orthogonal coordinate system shown in Figures 1 and 2 as appropriate. In this XYZ orthogonal coordinate system, the X and Y directions are horizontal directions, and the Z direction is vertical (up-down direction).
[0050] 1 and 2 show an example of an electronic component according to an embodiment. Fig. 1 is a perspective view of a multilayer ceramic capacitor 1, and Fig. 2 is a side cross-sectional view. The multilayer ceramic capacitor 1 includes a ceramic laminate 10 in which dielectric layers 12 and internal electrode layers 11 are alternately laminated, and an external electrode 20.
[0051] A method for manufacturing the multilayer ceramic capacitor 1 using the conductive paste will be described below. First, the conductive paste is printed on a dielectric green sheet and dried to form a dry film. A plurality of dielectric green sheets having this dry film on the upper surface are laminated by pressure bonding to obtain a laminate. Next, the laminate is fired and integrated to produce a ceramic laminate 10 in which the internal electrode layers 11 and the dielectric layers 12 are alternately laminated. After that, a pair of external electrodes 20 is formed on both ends of the ceramic laminate 10 to manufacture the multilayer ceramic capacitor 1. A more detailed description will be given below.
[0052] First, a dielectric green sheet, which is an unfired ceramic sheet, is prepared. For example, the dielectric green sheet is prepared by adding an organic binder such as polyvinyl butyral and a solvent such as terpineol to a raw powder of a specific ceramic such as barium titanate, applying the dielectric layer paste to a support film such as a PET film in a sheet form, and drying the paste to remove the solvent. The thickness of the dielectric green sheet is not particularly limited, but is preferably 0.05 μm or more and 3 μm or less from the viewpoint of the demand for miniaturization of the multilayer ceramic capacitor.
[0053] Next, the above-mentioned conductive paste is printed (applied) on one side of the dielectric green sheet by a known method such as screen printing, and then dried to form a dry film, to prepare a plurality of sheets. Note that, from the viewpoint of the requirement to make the internal electrode layer 11 thin, it is preferable that the thickness of the printed conductive paste (dry film) is 1 μm or less after drying.
[0054] Next, the dielectric green sheet is peeled off from the support film, and the dielectric green sheet and the dried film of the conductive paste formed on one side thereof are laminated so as to be alternately arranged, and then a laminate is obtained by a heat and pressure treatment. Note that a configuration may be adopted in which protective dielectric green sheets not coated with the conductive paste are further arranged on both sides of the laminate.
[0055] Next, the laminate is cut to a predetermined size to form green chips, and the green chips are subjected to a binder removal treatment and fired under a reducing atmosphere to produce the ceramic laminate 10. The binder removal treatment is preferably performed in air or N2 gas. The temperature during the binder removal treatment is, for example, 200°C or higher and 400°C or lower. The temperature is preferably held for 0.5 hours or higher and 24 hours or lower during the binder removal treatment. The firing is performed in a reducing atmosphere to suppress oxidation of the metal used in the internal electrode layers, and the temperature during firing of the laminate is, for example, 1,000°C or higher and 1,350°C or lower, and the temperature is held for, for example, 0.5 hours or higher and 8 hours or lower.
[0056] By firing the green chip, the organic binder in the green sheet is completely removed, and the ceramic raw material powder is fired to form the ceramic dielectric layer 12. The organic vehicle in the dried film is also removed, and the conductive powder such as nickel powder is sintered or melted and integrated to form an internal electrode, forming a multilayer ceramic sintered body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. Note that, from the viewpoint of taking oxygen into the dielectric layer to increase reliability and suppressing reoxidation of the internal electrodes, the sintered multilayer ceramic sintered body may be subjected to an annealing treatment.
[0057] A pair of external electrodes 20 is then provided on the produced fired laminated ceramic body to manufacture the laminated ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. The external electrode 20 is preferably made of, for example, copper, nickel, or an alloy thereof. The electronic component is not limited to a laminated ceramic capacitor, and may be an electronic component other than a laminated ceramic capacitor, such as a varistor. EXAMPLES
[0058] The present invention will be further described below based on examples and comparative examples of the present invention, but the present invention is not limited to the following examples in any way.
[0059] [Evaluation method] (Conductive paste viscosity) The viscosity of the conductive paste was measured using a rheometer (MCR501 manufactured by Anton Paar) after it was left to stand at room temperature (25°C) for 24 hours immediately after production. The viscosity of the conductive paste was measured at a shear rate of 4 s at 25°C. -1 Based on the measurement results, the paste viscosity was evaluated as follows.
[0060] ◎: Shear viscosity is 25 Pa s or more and 40 Pa s or less 〇: Shear viscosity is 20 Pa·s or more and less than 25 Pa·s, or more than 40 Pa·s and less than 60 Pa·s ×: Shear viscosity is less than 20 Pa·s or more than 60 Pa·s
[0061] (Dispersibility of conductive paste) The conductive paste thus produced was applied to a glass substrate in a thickness of 15 μm, and then heated and dried at 120°C for 10 minutes to obtain a dried film of the conductive paste. The surface of this dried film was observed using an optical microscope at a magnification of 100 (eyepiece, objective: 10x each), and the maximum particle size of the observed coarse particles (the longest diameter of the observed coarse particles) was measured. Based on the measurement results, the dispersibility was evaluated as follows.
[0062] ◎: The maximum particle size of coarse particles is 0.8 μm or less. Good: The maximum particle size of the coarse particles is greater than 0.8 μm and less than 1.0 μm. ×: The maximum particle size of the coarse particles exceeds 1.0 μm.
[0063] [Materials used] (conductive powder) The following materials were used as the conductive powder. Conductive powder 1: Ni powder (number average particle size 60nm) Conductive powder 2: Ni powder (number average particle size 30 nm) Conductive powder 3: Ni powder (number average particle size 100nm) Conductive powder 4: Cu powder (number average particle size 60nm)
[0064] (binder resin) The binder resin is ethyl cellulose resin (weight average molecular weight 44x10 3 ) (manufactured by Dow Chemical, trade name: ETHOCEL STD-4) was used.
[0065] (Additives) The following materials were used as additives, and the properties of the additives used are shown in Table 1. Additive 1: n-octyl acetoacetate (Tokyo Chemical Industry Co., Ltd.) Additive 2: n-octanoic acid (Tokyo Chemical Industry Co., Ltd.) Additive 3: Hexanoic acid (Tokyo Chemical Industry Co., Ltd.) Additive 4: Decanoic acid (Tokyo Chemical Industry Co., Ltd.) Additive 5: 2-ethylhexanoic acid (Tokyo Chemical Industry Co., Ltd.) Additive 6: Butyric acid (Tokyo Chemical Industry Co., Ltd.) Additive 7: Phosphoric acid (Tokyo Chemical Industry Co., Ltd.) Additive 8: Formic acid (Tokyo Chemical Industry Co., Ltd.) Additive 9: Octane (Tokyo Chemical Industry Co., Ltd.) Additive 10: Stearic acid (Tokyo Chemical Industry Co., Ltd.)
[0066] [Table 1]
[0067] (Organic solvent) Dihydroterpineol was used as the organic solvent.
[0068] (ceramic powder) Barium titanate (average particle size: 10 nm) was used as the ceramic powder.
[0069] [Example 1] A vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol) was prepared so that the binder resin component was 10% by mass. Then, with respect to the total mass of the conductive paste, 45% by mass of conductive powder 1 (Ni powder: average particle size 60 nm), 1% by mass of additive 1 (n-octylacetoacetate: manufactured by Tokyo Chemical Industry Co., Ltd.), 30% by mass of a vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol), and the remainder being dihydroterpineol were mixed so that the total was 100% by mass. These materials were kneaded with a three-roll mill to prepare the conductive paste described in Example 1. The composition of the materials is shown in Table 2.
[0070] [Examples 2 to 9] A conductive paste was prepared in the same manner as in Example 1, except that the types and amounts of materials were changed as shown in Table 2. The evaluation results are shown in Table 2.
[0071] [Example 10] A vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol) was prepared so that the binder resin component was 40% by mass. Then, with respect to the total mass of the conductive paste, 65% by mass of conductive powder 1 (Ni powder: average particle size 60 nm), 2.5% by mass of additive 1 (n-octylacetoacetate: manufactured by Tokyo Chemical Industry Co., Ltd.), 25% by mass of a vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol), and the remainder being dihydroterpineol were mixed so that the total was 100% by mass. These materials were kneaded with a three-roll mill to prepare the conductive paste described in Example 10. The evaluation results are shown in Table 2.
[0072] [Example 11] A conductive paste was prepared in the same manner as in Example 10, except that the types and amounts of materials were changed as shown in Table 2. The evaluation results are shown in Table 2. [Examples 12 to 16] A conductive paste was prepared in the same manner as in Example 1, except that the types and amounts of materials were changed as shown in Table 2. The evaluation results are shown in Table 2.
[0073] [Example 17] A vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol) was prepared so that the binder resin component was 10% by mass. Then, with respect to the total mass of the conductive paste, 45% by mass of conductive powder 1 (Ni powder: average particle size 60 nm), 1% by mass of additive 1 (n-octylacetoacetate: manufactured by Tokyo Chemical Industry Co., Ltd.), 5% by mass of ceramic (average particle size: 10 nm), 30% by mass of a vehicle consisting of a binder resin (ethyl cellulose resin) and an organic solvent (dihydroterpineol), and the remainder was dihydroterpineol, and the total was mixed so that the total was 100% by mass. These materials were kneaded with a three-roll mill to prepare the conductive paste described in Example 17. The evaluation results are shown in Table 2.
[0074] [Comparative Example 1] Except for not using the additive, the conductive paste was prepared in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0075] [Comparative Examples 2 to 6] A conductive paste was prepared in the same manner as in Example 1, except that the types and amounts of materials were changed as shown in Table 2. The evaluation results are shown in Table 2.
[0076] [Table 2]
[0077] [Evaluation Results] As shown in Tables 1 and 2, the conductive paste of the embodiment, which does not contain N atoms and uses additives having structures (A) and (B), has a viscosity suitable for screen printing, and the number of coarse particles on the surface of the dried film is reduced, resulting in good dispersibility.
[0078] On the other hand, the conductive paste of Comparative Example 1, which did not contain any additive, had a shear viscosity of more than 60 Pa·s, and coarse particle sizes of 1.0 μm or more were formed on the surface of the dried film, indicating poor dispersibility.
[0079] Furthermore, the conductive pastes of Comparative Examples 2 to 4, which used additives having a carboxylic acid or phosphate structure but with a hydrocarbon group having 4 or less carbon atoms or no hydrocarbon group, and the conductive paste of Comparative Example 5, which had a chain hydrocarbon (8 carbon atoms) but no structure (B), had shear viscosities of 20 Pa s or more and less than 25 Pa s, or more than 40 Pa s and 60 Pa s or less, and coarse particle sizes of 1.0 μm or more were formed on the dried film surface, indicating insufficient dispersibility.
[0080] In addition, in the conductive paste of Comparative Example 6, which had structure (B) but used an additive having a chain hydrocarbon group with more than 10 carbon atoms, visually visible aggregates (coarse particles) were observed in the conductive paste, so the above-mentioned shear rate and dispersibility were not evaluated.
[0081] In addition, Fig. 3 shows an observation image of the surface of the dried film of Example 1, and Fig. 4 shows an observation image of the surface of the dried film of Comparative Example 2. As shown in Figs. 3 and 4, in the dried film of Example 1, the formation of coarse particles was significantly suppressed compared to the dried film of Comparative Example 2.
[0082] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. In addition, to the extent permitted by law, the disclosures of all documents cited in the above-mentioned embodiments are incorporated by reference and are included as part of the description in this text. [Explanation of symbols]
[0083] 1. Multilayer ceramic capacitor 10...Ceramic laminate 11...Internal electrode layer 12...Dielectric layer 20…External electrode 21...External electrode layer 22…Plating layer
Claims
1. A conductive paste comprising a conductive powder, a binder resin, an additive, and an organic solvent, The additive has a structure (A) of a chain hydrocarbon group having 5 to 9 carbon atoms and at least one structure (B) selected from phosphoric acid, carboxylic acid, and β-keto ester, and does not contain a N atom; The conductive paste is subjected to a shear rate of 4 s at 25°C. -1 The conductive paste has a shear viscosity of 20 Pa·s or more and 60 Pa·s or less.
2. The conductive paste according to claim 1 , wherein the content of the additive is 0.01 parts by mass or more and 4 parts by mass or less with respect to 100 parts by mass of the conductive powder.
3. 3. The conductive paste according to claim 1, wherein the conductive powder is present in an amount of 40 mass % or more and 65 mass % or less based on a total amount of the conductive paste.
4. The conductive paste according to claim 1 or 2, wherein the conductive powder has a number average particle size of 120 nm or less.
5. The conductive paste according to claim 1 or 2, wherein the conductive powder is at least one selected from the group consisting of gold powder, silver powder, palladium powder, copper powder, nickel powder, aluminum powder, silver-palladium alloy powder, copper alloy powder and aluminum alloy powder.
6. The conductive paste according to claim 1 or 2, wherein the binder resin comprises at least one selected from the group consisting of a cellulose-based resin and an acetal-based resin.
7. 3. The conductive paste according to claim 1, wherein the content of the organic solvent in the conductive paste is 20% by mass or more and 60% by mass or less.
8. The conductive paste according to claim 1 or 2, further comprising a ceramic powder.
9. 9. The conductive paste according to claim 8, wherein the ceramic powder is at least one selected from the group consisting of aluminum oxide powder, zinc oxide powder, titanium oxide powder, mullite powder, barium titanate powder, lead zirconate titanate powder, and silicate glass powder.
10. An electronic component formed by using the conductive paste according to claim 1 or 2.
11. 9. A multilayer ceramic capacitor comprising at least a laminate in which dielectric layers and internal electrode layers are laminated, the internal electrode layers being formed using the conductive paste according to claim 8.
Citation Information
Patent Citations
Production method of conductive paste and conductive paste obtained by the method
JP2016031912A